Mesenchymal stem cells alleviate hypoxia-induced oxidative stress and enhance the pro-survival pathways in porcine islets - Tan, Yixiong (Exp Biol Med (Maywood), 2019)
Islet transplantation is a promising treatment for selected patients with type 1 diabetes mellitus (T1DM). Hypoxia and oxidative stress are major causes of damage to transplanted islets. Mesenchymal stem cells (MSCs) have been shown to enhance cell survival mainly through paracrine secretion. However, mechanisms of action underlying the protective effects of MSCs on islets have not been fully elucidated. In this study, we investigated whether human umbilical cord-derived MSCs (huc-MSCs) could inhibit hypoxia and ROS-related cell death of neonatal porcine islet cell clusters (NICCs) and further determined the underlying molecular mechanisms. NICCs were cultured in vitro under normoxic and hypoxic (1% O(2)) conditions with or without MSC-conditioned medium (MSC-CM). Apoptosis of NICCs was evaluated by the AO/EB staining and Annexin V/PI flow cytometry analysis. Total and mitochondrial ROS production was detected by fluorometric assays. Western blot and the ERK pathway inhibitor, PD98059, were used to assess the possible pathways involved. The results showed that MSC-CM suppressed hypoxia-induced oxidative stress and cell death of NICCs. MSC-CM also activated several pro-survival pathways in NICCs under hypoxic conditions. Furthermore, MSC-secreted exosomes and IL-6 partially recapitulated the multifunctional benefits of MSC-CM. This study showed that huc-MSCs protected NICCs from hypoxia-induced cell death by regulating the cell redox state and cell signaling pathways. This increased understanding may enable MSCs to become a more promising adjuvant cell therapy for islet transplantation. IMPACT STATEMENT: The utilization of mesenchymal stem cells (MSCs) is a promising approach to serve as adjuvant therapy for islet transplantation. But the inability to translate promising preclinical results into sound therapeutic effects in human subjects indicates a lack of key knowledge of MSC-islet interactions that warrant further research. Hypoxia and oxidative stress are critical factors which lead to a tremendous loss of islet grafts. However, previous studies mainly focused on other aspects of MSC protection such as inducing revascularization, enhancing insulin secretion, and reducing islet apoptosis. In this study, we aim to investigate whether MSC can protect islet cells from hypoxic damage by inhibiting ROS production and the potential underlying pathways involved. We also explore the effects of MSC-derived exosomes and IL-6 on hypoxia-injured islets. Our data provide new molecular targets for developing MSC applications, and this may ultimately promote the efficiency of clinical islet transplantation.